Synthesis of magnetic nanoparticles coated zirconia using one-pot solvothermal processes as adsorbent for Pb(II) and Cd(II) removal - Chairul Irawan; Muhammad Fuad Refki; Rafiq Hidayat; Ridhayanti Mu'minah; Iryanti Fatyasari Nata; Meilana Dharma Putra; Agus Triantoro (South African Journal of Chemical Engineering, 2023)
Indonesia, notably in Central Kalimantan, has the potential for raw zirconia mineral, but it has not been successfully developed as a material that has ecologically friendly, high economic and technical value. The magnetic nanoparticles coated zirconia mineral was synthesized by using one-pot solvothermal processes, and then was used as adsorbent for water and wastewater treatment in adsorption process. Zirconia minerals are turned into composites with magnetic nanoparticles with the addition of hexane diamine to create the composite with amino groups (MH@ZrO2). It was then utilized as adsorbent to adsorb lead and cadmium metal in an artificial solution, and lower the metal content of lead/ (Pb(II)) and cadmium (Cd(II)) in it. The first stage was to determine the equilibrium of contact time (30, 60, 120, 240, and 360 min) of the adsorbent in binding Pb(II) and Cd(II) ions. The variations of pH 3, 5, 7, and 9 in the solution during adsorption were also examined to establish appropriate conditions for the adsorption process. The observations of magnetic nanoparticles composites based on a Scanning Electron Microscopy (SEM) analysis showed that magnetic nanoparticles with the diameter of 30–50 nm were generated on the face of zirconia minerals. X-Ray Diffraction (X-RD) analysis revealed that zirconia minerals treatment lowered the Crystallinity Index by 11.19% and the silica content by 98%. A Fourier Transform Infra-Red (FT-IR) spectrometer showed an adsorption peak of 590 cm−1 for the Fe-O bond on Fe3O4. Meanwhile, the optimum condition for Pb(II) and Cd(II) adsorption with pHe around 7 ± 0.2 for 360 min resulted in an adsorption density of 117.67 mg/g and 24.19 mg/g, respectively. The MH@ZrO2 led to development for high potential adsorbent due to stable material and easy separation, and capable for absorbing Pb(II) and Cd(II) ions from an aqueous solution.